STRATEGIC MANAGEMENT OF BIOCHEMICAL AND BIOPHYSICAL CONTROL STRUCTURES AND SUSTAINABILITY HEALTH ACHIEVEMENT - Ioana-Andreea, MARINESCU; Cicerone-Nicolae, MARINESCU (Strategii Manageriale)
Scientific Investigation of sustainability sanitary herein, matters to a) define the structure of the health sector; b) knowing the contents of the local health systems, c) to obtain information about the properties and characteristics associated with health in Romania; d) obtaining views on the mission, objectives, goals and targets pursued by health services; e) scheduling results, effects and positive consequences among human communities to ensure sustainable health in the framework of sustainable development of the country and, last but not least; f) it is intended to measure people's participation and the rule management process, based on biochemical and biophysical control structures. Mainly, it is considered that the sustainability and health have depicted conceptual content that must be secured effectively recovered, concrete operational activities of health systems in laboratories and hospitals.